2021
DOI: 10.1002/hon.2838
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab vedotin plus doxorubicin, vinblastine, and dacarbazine in patients with advanced‐stage, classical Hodgkin lymphoma: A prespecified subgroup analysis of high‐risk patients from the ECHELON‐1 study

Abstract: Approximately one‐third of patients diagnosed with Hodgkin lymphoma presenting with Stage IV disease do not survive past 5 years. We present updated efficacy and safety analyses in high‐risk patient subgroups, defined by Stage IV disease or International Prognostic Score (IPS) of 4–7, enrolled in the ECHELON‐1 study that compared brentuximab vedotin plus doxorubicin, vinblastine, and dacarbazine (A + AVD) versus doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) as first‐line therapy after a median fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A prespecified subgroup analysis confirmed that BV-AVD was associated with consistent improvement in PFS at 3 years among patients in high-risk subgroups, as assessed by the investigator (hazard ratio [HR], 0.723 for patients with stage IV disease; P5.032; HR, 0.588 for patients with IPS 4-7; P5.012). 47 The 3-year PFS rate in patients with an IPS of 4-7 was 79.6% in the BV-AVD group compared with 65.7% for ABVD group. Patients in the high-risk subgroups did not experience greater incidences of treatment-related adverse events (trAEs) than the total population.…”
Section: Secondary Malignancies Fmentioning
confidence: 84%
See 1 more Smart Citation
“…A prespecified subgroup analysis confirmed that BV-AVD was associated with consistent improvement in PFS at 3 years among patients in high-risk subgroups, as assessed by the investigator (hazard ratio [HR], 0.723 for patients with stage IV disease; P5.032; HR, 0.588 for patients with IPS 4-7; P5.012). 47 The 3-year PFS rate in patients with an IPS of 4-7 was 79.6% in the BV-AVD group compared with 65.7% for ABVD group. Patients in the high-risk subgroups did not experience greater incidences of treatment-related adverse events (trAEs) than the total population.…”
Section: Secondary Malignancies Fmentioning
confidence: 84%
“…e Active bone marrow can be delineated using various imaging modalities and is most abundant in the pelvic bones, thoracic-lumbar spine, and sacrum. [47][48][49]…”
Section: Rt Dose Constraint Guidelines For Lymphoma Bmentioning
confidence: 99%
“…Brentuximab vedotin (A) in combination with AVD, an alternative 1L treatment option, is associated with substantially less pulmonary toxicity than ABVD, however myelotoxicity and neurotoxicity are increased (although myelotoxicity can be ameliorated with prophylactic G‐CSF and neurotoxicity is largely reversible). The A+AVD combination appears to be more effective than ABVD for 1L treatment of advanced‐stage cHL [14, 33, 34], and may have a role in treatment of older cHL patients and those with high IPS stage [35, 36], who tend to have less favorable outcomes as shown in this study.…”
Section: Discussionmentioning
confidence: 90%
“…A + AVD was also associated with numerically fewer second primary malignancies compared with ABVD, as well as a greater number of pregnancies, suggesting no additional risk of infertility [13]. Subgroup analyses from ECHELON-1 assessed the efficacy and safety of A + AVD as first-line treatment in older and high-risk patients [17,18]. In adults ≥ 60 years of age, a group for whom outcomes have historically been poor, modified PFS at 24 months was statistically similar between the A + AVD and ABVD arms [17].…”
Section: Brentuximab Vedotin For First-line Treatment Of Chlmentioning
confidence: 99%
“…Subgroup analyses from ECHELON-1 assessed the efficacy and safety of A + AVD as first-line treatment in older and high-risk patients [ 17 , 18 ]. In adults ≥ 60 years of age, a group for whom outcomes have historically been poor, modified PFS at 24 months was statistically similar between the A + AVD and ABVD arms [ 17 ].…”
Section: Brentuximab Vedotin For First-line Treatment Of Chlmentioning
confidence: 99%